Dihydroouabain, a novel radiosensitizer for cervical cancer identified by automated high-throughput screening. (July 2020) - Li, Zhihao; Tamari, Keisuke; Seo, Yuji; Minami, Kazumasa; Takahashi, Yutaka; Tatekawa, Shotaro; Otani, Keisuke; Suzuki, Osamu; Isohashi, Fumiaki; Ogawa, Kazuhiko
Highlights: An efficient, feasible method for identifying new radiosensitizers was established. Dihydroouabain (DHO) is a radiosensitizer identified by high-throughput screening. DHO abrogated radiation-induced S phase arrest. Combination treatment significantly increased Chk1 inhibition and DSB response. Abstract: Background and purpose: Radiotherapy plays a crucial role in the treatment of cervical cancer, but existing radiosensitizers have limited efficacy in clinical applications. The aims of this study were to establish and verify an efficient method for identifying new radiosensitizers, to use this to identify candidate radiosensitizers for cervical cancer, and to investigate the specific mechanisms of these when used in combination with radiotherapy. Materials and methods: An automated platform for identifying radiosensitizers for cervical cancer was created based on high-throughput screening technology. The radiosensitizing effects of candidate compounds from the LOPAC1280 chemical library were evaluated in radiosensitive and radioresistant cervical cancer cells using a clonogenic survival assay, with cell cycle analyses, and western blot analyses performed for both cell lines. Results: The automated high-throughput screening approach identified four hit compounds. One of the most potent candidates was dihydroouabain (DHO), an inhibitor of Na + /K + -ATPase that has not previously been classified as a radiosensitizer. DHO significantly enhanced radiosensitivity in cervical cancer cells. It also abrogated radiation-induced S phase arrest in cervical cancer cells. Combination treatment significantly caused the inhibition of Chk1 and increased DNA double-strand breaks (DSB). Conclusions: DHO is a novel radiosensitizer for the treatment of cervical cancer. The automated high-throughput screening platform developed in this study proved to be powerful and effective, with the potential to be widely used in the future identification of radiosensitizers.